Challenges in Designing Personalised Learning Paths in SPOCs - Anne Kristine Petersen; Peter Gundersen (Stockholm University Press, 2019)
The paper explores the challenges of designing personalised learning paths in SPOCs (Small Private Online Courses). It opens with a discussion on different approaches to tailoring teaching to individual needs and moves on to introduce a SPOC that was developed for Continuing Professional Development (CPD) for primary and lower-secondary teachers in Denmark. The SPOC, which performs adaptation using a recommendation system, allows for students to create a personalised learning path on the basis of three components: a learner profile, a content model and an adaptation model. Using the three components as a starting point, the SPOC is analysed in order to identify differences between the intended design (what the SPOC set out to do), the implemented design (how the SPOC is used by its users) and the attained design (the outcome of the SPOC). The analysis draws on data from a series of semi-structured interviews with SPOC students and their lecturers. We find that the implemented design deviates from the intended design in several respects, most notably in relation to how the personalised learning paths are created and how decisions as to curriculum contents are made. Moreover, it is suggested that differences between the intended design and the implemented design are rooted in differences in the learning perspectives of the students, the lecturers and the educational designers of the SPOC. Despite the fact that the implemented design deviates from the intended design, the attained design is nevertheless successful in that a high percentage of the students enrolled succeeded in passing their examinations and thus obtained the formal qualifications in the subjects they teach. It is concluded that further research in adaptive learning designs for online platforms such as MOOCs (Massive Open Online Course) and SPOCs is needed to minimise the gap between intended designs and implemented designs in order to create a more personalised learning experience for the students involved.